2013
DOI: 10.1371/journal.pone.0054120
|View full text |Cite
|
Sign up to set email alerts
|

Life History Trade-Offs and Behavioral Sensitivity to Testosterone: An Experimental Test When Female Aggression and Maternal Care Co-Occur

Abstract: Research on male animals suggests that the hormone testosterone plays a central role in mediating the trade-off between mating effort and parental effort. However, the direct links between testosterone, intrasexual aggression and parental care are remarkably mixed across species. Previous attempts to reconcile these patterns suggest that selection favors behavioral insensitivity to testosterone when paternal care is essential to reproductive success and when breeding seasons are especially short. Females also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 96 publications
(123 reference statements)
6
83
0
Order By: Relevance
“…This life-history tradeoff is believed to be mediated in part by T, which increases singing and mate-finding and decreases parental behavior in many seasonally breeding sparrows (27)(28)(29)(30). In free-living populations of white-throated sparrows, plasma T levels are higher in WS birds (7,8), which have the ZAL2 m rearrangement, than in TS birds, which do not (2,31).…”
Section: Discussionmentioning
confidence: 99%
“…This life-history tradeoff is believed to be mediated in part by T, which increases singing and mate-finding and decreases parental behavior in many seasonally breeding sparrows (27)(28)(29)(30). In free-living populations of white-throated sparrows, plasma T levels are higher in WS birds (7,8), which have the ZAL2 m rearrangement, than in TS birds, which do not (2,31).…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to a previous study in tree swallows that experimentally elevated T levels of females during incubation and reported cooler nest temperatures and complete hatching failure (Rosvall, 2013). Female great tits implanted with T during nest building also had lower incubation temperatures and hatching success (de Jong et al, 2016), but such negative effects of T on incubation behaviour were not observed in female dark-eyed juncos implanted prior to breeding (Clotfelter et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…T has been shown to have masculinizing effects on female traits in a variety of taxa, although whether such changes reduce their attractiveness to potential mates is unclear (Ketterson et al, 2005;Lahaye et al, 2013). Given that exogenous T increases aggressive behaviour in female tree swallows (Rosvall, 2013), in my study T-treated female tree swallows likely spent more time involved in aggressive interactions and territory defence, as previously suggested for spotless starlings (García-Vigón et al, 2008), rather than seeking extra-pair copulations.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations